2020
DOI: 10.1186/s40644-020-00366-3
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and possible value of quantitative semi-automated diffusion weighted imaging volumetry of neuroblastic tumors

Abstract: Background To assess the feasibility and possible value of semi-automated diffusion weighted imaging (DWI) volumetry of whole neuroblastic tumors with apparent diffusion coefficient (ADC) map evaluation after neoadjuvant chemotherapy. Methods Pediatric patients who underwent surgical resection of neuroblastic tumors at our institution from 2013 to 2019 and who received a preoperative MRI scan with DWI after chemotherapy were included. Tumor volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
1
8
1
Order By: Relevance
“…Automated software are now available to provide a voxel-base three-dimensional mean of tumor ADC values making it an easy parameter to evaluate. 17 Although, our studies did not find a statically significant difference between DNETs and gangliogliomas, few studies available have shown that DNETs might have the highest ADC values among all parenchymal neoplasm. Larger studies are needed to further characterize the different tumors under the MNGTs umbrella on DWI.…”
Section: Discussioncontrasting
confidence: 73%
“…Automated software are now available to provide a voxel-base three-dimensional mean of tumor ADC values making it an easy parameter to evaluate. 17 Although, our studies did not find a statically significant difference between DNETs and gangliogliomas, few studies available have shown that DNETs might have the highest ADC values among all parenchymal neoplasm. Larger studies are needed to further characterize the different tumors under the MNGTs umbrella on DWI.…”
Section: Discussioncontrasting
confidence: 73%
“…In our study, expert tumor delineation performed as the best (although not perfect) approach to truth. The evaluation of the voxel-wise similarity between the ground truth and the automatically segmented mask demonstrates that the state-of-the-art deep learning architecture nnU-Net can be used to detect and segment neuroblastic tumors on MR images, with a median DSC of 0.965 (±0.018 IQR), achieving a strong performance and surpassing the methods and results obtained in previous studies that approached the problem of neuroblastoma segmentation [ 9 , 10 , 11 ]. However, no previous literature has demonstrated the performance of a CNN-based solution in neuroblastic tumor.…”
Section: Discussionmentioning
confidence: 80%
“…In the case of neuroblastic tumors, several studies have explored the development of semiautomatic segmentation algorithms. They have been performed on Computed Tomography (CT) or MR images, making use of mathematical morphology, fuzzy connectivity and other imaging processing tools [ 9 , 10 , 11 ]. However, they have included a very low number of cases and the findings show little improvement with respect to manual approaches.…”
Section: Introductionmentioning
confidence: 99%
“…GNs can also develop from infant neuroblastoma via maturation [14]. The MRI sequence of DWI and ADC mapping is of utmost importance for the differentiation between neuroblastoma, ganglioneuroblastoma, and ganglioneroma [15,16].…”
Section: Discussionmentioning
confidence: 99%